Diversity and Geographic Distribution of Ligninolytic Fungi Associated With Castanopsis sieboldii Leaf Litter in Japan - Osono, Takashi; Matsuoka, Shunsuke; Hirose, Dai (Frontiers in Microbiology, 2020)
The diversity and geographic pattern of ligninolytic fungi were investigated within the distribution range of an evergreen tree, Castanopsis sieboldii (Fagaceae), in Japan. Fungal isolates obtained from 18 sites in subtropical and temperate regions in Japan were classified into 50 operational taxonomic units in Ascomycota and Basidiomycota according to the base sequence of the rDNA internal transcribed spacer region. Ordination by nonmetric multidimensional scaling showed the separation of fungal compositions between the study sites which was significantly related to the latitude, longitude, and mean annual temperature of the study sites. We applied variation partitioning to separate the magnitude of the climatic, spatial, and leaf property factors and found the roles of mean annual temperature and spatial factors in structuring fungal assemblages, suggesting the importance of both niche processes and such non-niche processes as priority effect and dispersal limitation. The bleached area on leaf litter was greater at sites with higher mean annual temperature and precipitation located at lower latitudes and at sites where some major ligninolytic fungi occurred at greater relative frequencies, indicating that not only the climatic conditions but also the biogeographic patterns of distribution of ligninolytic fungi influence the decomposition of lignin in leaf litter.